Evidence From the words of God Almighty (And remember God during the appointed days) (Journal of the College of Basic Education, 2026)
Worship and obedience are diverse in Islamic law. These acts of worship are performed to remember God Almighty, and glorifying them demonstrates piety of heart. Hajj is one of these acts of worship, a great pillar that encompasses many rituals. These rituals contain noble legislation and blessed Sunnahs that keep Muslims constantly remembering God Almighty. These rituals include the blessed Days of Tashreeq, during which God Almighty commanded pilgrims to frequently remember Him, glorifying Him and expressing gratitude for His bounty. These acts of worship are diverse, all of which involve remembrance and glorification of God, Lord of the Worlds.This research explains the meanings of remembrance of God Almighty and the days on which God Almighty commanded frequent remembrance. This remembrance is a glorification of the Days of Tashreeq and a glorification of the blessings of God Almighty bestowed upon the pilgrims to His House and those visiting His sacred sanctuary.